Law of Trading in Mother’s Milk Perspective of Shafi'i Mazhab In Makassar - Arsy, Muhammad; Normiati, Normiati (Manunggal Halim Jaya, 2024)
This study aims to determine the factors and analyze to find out the legal basis regarding trade in mother’s milk. And to find out the views of the schools of thought regarding the Trade of mother’s milk. This research uses normative research methods. Data collection in this study is the view of the schools of thought regarding the Trade of mother’s milk (breast feed). The results of this study indicate that Imam Hanafi and Hanbali that Trade in mother’s milk is prohibited, because mother’s milk is a part of the human body as well as blood, eyes and other body parts. In addition, mother’s milk is also not a market object that can be traded, so it is forbidden to be traded. Meanwhile, according to Iman Maliki and Imam Syafi'i, it is permissible to buy and sell mother’s milk, because mother’s milk is a sacred object and can be used for babies, and it is lawful to drink it, so it can also be traded like sheep's milk. In addition, the difference is in the sacred as a condition for the validity of the object being traded and having a sale value. Imam Maliki and Shafi'i made it sacred and useful as a condition for the validity of the object being traded. Meanwhile, according to Imam Hanafi and Hanbali that sacred objects cannot necessarily be traded, for example natural water. Likewise with breast feed.